Estrogen related receptor alpha triggers the migration and invasion of endometrial cancer cells via up regulation of TGFB1. Issue 6 (2nd November 2018) - Huang, Xiumin; Wang, Xuelian; Shang, Jing; Zhaang, Zhiqin; Cui, Binbin; Lin, Yanzhen; Yang, Ying; Song, Youyi; Yu, Shengnan; Xia, Junjie
ABSTRACT: Estrogenic signals have been suggested to be important for the tumorigenesis and progression of endometrial cancer (EC) cells. Our present data showed that estrogen related receptor alpha (ERRα), while not ERRβ or ERRγ, was significantly elevated in EC cells and tissues when compared to their controls. Targeted inhibition of ERRα by siRNA or its inverse agonist XCT-790 can suppress the migration and invasion of EC cells. Both si-ERRα and XCT-790 decreased the expression of transforming growth factor-beta (TGF-β). ERRα can directly bind with the promoter of TGFB1 and then increase its transcription. Further, ERRα was involved in the positive self-feedback loop of TGF-β in EC cells. Targeted inhibition of ERRα/TGF-β can synergistically suppress the in vitro invasion of EC cells. Collectively, our data suggested that ERRα can trigger the cell migration and invasion via increasing the positive self-feedback regulation of TGF-β.